Synthesis of La2(C2O4)3 nanoprisms decorated with Fe3O4@m(ZrO2‐CeO2) nanospheres and their application for effective fluoride removal. Issue 11 (2nd September 2019) - Wang, Tao; Chen, Pinghua; Li, Menglin; Luo, Xubiao; Liu, Lingling; Zeng, Guisheng; Jiang, Jianyuan; Huang, Keyi; Xu, Xueyuan; Li, Songjun; Jiang, Hualin
Abstract: BACKGROUND: Composites of defluoridation adsorbents based on rare earths have attracted increasing interest recently, but most of them were amorphous. The main reason for this situation is that morphology control has not been paid enough attention, because the related preparation methods are relatively sparse. Consequently, novel preparation methods are urgently needed. RESULTS: In this study, a novel La‐Zr‐Ce tri‐metal adsorbent with regular morphology was facilely synthesized. There were two morphological shapes in the composite. Nanoprisms of La2 (C2 O4 )3 were decorated with mesoporous nanospheres of Fe3 O4 @m(ZrO2 ‐CeO2 ). The samples were investigated by energy‐dispersive spectroscopy (EDS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X‐ray diffraction (XRD), vibrating sample magnetometer (VSM) and X‐ray photoelectron spectroscopy (XPS). Several affecting factors such as initial fluoride concentration, contact time, coexisting anions and pH were studied in detail. The balance data were analyzed by Langmuir, Freundlich and Langmuir–Freundlich isotherm models. The nanocomposite had a maximum sorption capacity of 117.3 mg g −1 toward fluoride, which is among the highest ever reported for fluoride adsorbents. Furthermore, it had a wide applicable pH range of 2–10 and high anti‐interference ability. The different functions of La2 (C2 O4 )3 nanoprisms and Fe3 O4 @m(ZrO2 ‐CeO2 ) nanospheres in the composite have been elucidated. These two components were found to synergistically improve F − adsorption performance via their individual merits. CONCLUSION: The adsorbent had high potential to treat F − contaminants in real application, and the method reported here is considered to be helpful for developing more highly effective adsorbents. © 2019 Society of Chemical Industry